Determinants of financial performance: reviewed from financial structure and dividend policy - Rahman, Karlina Ghazalah; Rahman, Moch Ridho Ghazali; Mus, Abdul Rahman (Enrichment : Journal of Management, 2024)
This study was conducted to analyze the relationship between financial structure and dividend policy on financial performance. The grand theories used are trade-off theory and dividend irrelevance theory. The research method used is quantitative with a causal analysis approach. This study used secondary data with a purposive sampling method, the sample of this study was 32 companies with the amount of data observed as many as 128 data. The results of this study show that: (1) Financial structure has a positive and significant effect on the company's financial performance; (2) Dividend policy has a negative and significant effect on the company's financial performance.